Development and characterization of 𝐌n-doped 𝐂uS𝐂N hole transport material - Hathurusingha, K. (University of Jaffna, 2022)
Pure and manganese (Mn)doped CuSCN thin-films were prepared by using dimethyl sulfoxide (DMSO) as the solvent via the doctor blade method, and their electrical, optical, and structural properties were characterized. Mn-doped CuSCN thin-films were prepared with Mn mass percentages as 2 %, 4 %, 6 %, 8 %, and 10 %. Structural and optical properties were characterized by using XRD and UV-Visible spectrometers. According to the sheet resistance value for the unit area of thin films, conductivity gradually increased with Mn concentration in samples up to the doping concentration of 6 % and this mass percentage of CuSCN sample exhibited the highest conductivity value. The calculated crystalline size for pure CuSCN is 70.7 nm and, 28.3 nm for the 10 % doped sample. It reveals that the crystalline size decreased with the increase of Mn concentration. All the Pure and Mn-doped CuSCN thin-films show the absorbance in the UV-Visible wavelength region of the spectrum. The calculated optical energy bandgap of CuSCN is 3.18 eV, and it exists within the semiconductor region and can be considered as a wide bandgap semiconductor. Hence, the Mn-doped CuSCN layer can be used as an efficient hole transport material (HTM) layer in dye-sensitized solar cells and other applications.
Keywords: Copper thiocyanate; Electrical conductivity; Manganese; Optical bandgap